Sn Substitution by Ge: Strategies to Overcome the Open-Circuit Voltage Deficit of Kesterite Solar Cells - Choubrac, Leo; Bär, Marcus; Kozina, Xeniya; Felix, Roberto; Wilks, Regan G.; Brammertz, Guy; Levcenko, Sergiu; Arzel, Ludovic; Barreau, Nicolas; Harel, Sylvie; Meuris, Marc; Vermang, Bart (ACS Applied Energy Materials, 2020)
Current state-of-the-art Cu2ZnSn(S,Se)(4) kesterite solar cells are limited by low open-circuit voltages (V-OC). In order to evaluate to what extent the substitution of Sn by Ge is able to result in higher V oc values, this article focuses on Cu2ZnGeSe4 "CZGSe" devices. To reveal their full potential, different strategies are explored that, in particular, aim at the optimization of the CZGSe/buffer heterojunction. Here, employing hard X-ray photoelectron spectroscopy, it is evidenced that only a combination of different surface treatments is able to remove all detrimental secondary phases. Further improvements are achieved by establishing a solar cell heat treatment in air. A systematic study of the impact of different annealing temperatures and durations determines the best heat treatment parameters to be 60 min at 200 degrees C. Also, Zn(O,S,OH) as a more transparent alternative to the heavy-metal compound CdS buffer layer has been realized. Combining all of the strategies, solar cells with 8.5 and 7.5% total area efficiency have been prepared, which is a record for Sn-free kesterite solar cells and any kesterite solar cell with a Zn(O,S,OH) buffer, respectively. Beyond these records, this work clearly confirms the emerging trend that Ge-for-Sn substitution is a successful strategy to improve the V-OC of kesterite solar cells.
CRIS-Team WoS Importer:2020-07-17